Hardness Analysis of Aluminium 5083 A-TIG Welding Due to The Effect of Active Flux and Current - Eriek Widodo; Dika Anggara; Moch. Karim Al Amin; M. Idris Al Jawwad (Politeknik Negeri Lhokseumawe, 2023)
Aluminium allow has been widely used recently due to their high strength to mass ratio, good formability and high corrosion resistance have a wide range of applications in aerospace, ship-building and railway industries. The 5083 series aluminum is the most widely used due to good strength and corrosion resistance properties. Tungsten Inert Gas Welding (TIG welding) is the most common welding method for aluminum alloys. This research was conducted A-TIG welding on 150 x 100 x 8 mm of 5083 aluminium and added by oxide powder (MgCl2 and TiO2) as active flux and various of current consist of 100, 130, and 160 A. The result of this research was obtained that the deepest penetration was 4.94 mm with TiO2 active flux and the current of 160 A, the highest hardness came from weld metal which using MgCl2 as an active flux with 100 A of current with 69.80 HVN. The hardness was increased by adding magnesium due to effect of it could be increased grain coarse. The lowest hardness was on weld metal with TiO2 active flux with 160 A of current due to the maximum heat input which decreased the hardness The recrystallization was occurred due to increase of heat input, so did the grain growth. The coarse grain which caused the decreasing of hardness was affected by the increase of heat input.